1985
DOI: 10.1037/0022-3514.49.1.135
|View full text |Cite
|
Sign up to set email alerts
|

Women's involvement in multiple roles and psychological distress.

Abstract: Women's involvement in multiple roles was examined in relation to three stress indices: role overload, role conflict, and anxiety. Using hierarchical multiple regression analyses, effects of number of roles occupied; occupancy of the particular roles of paid worker, wife, and mother; and the quality of a woman's experience in her roles were analyzed. Data were from a disproportionate stratified random sample (N = 238) of Caucasian women between 35 and 55 years of age. For the total sample and for employed wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
306
1
17

Year Published

1993
1993
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 416 publications
(338 citation statements)
references
References 14 publications
14
306
1
17
Order By: Relevance
“…As may be noticeable, neither work to family conflict, nor family to work conflict have manifested themselves as important in the relationship with life satisfaction, which may be understood in terms of the expansionist hypothesis, which suggested that the advantages of pursuing multiple roles (from work to family, and vice versa) are likely to outweigh the disadvantages [52] [53] [54]. The results have supported this assumption as only enrichment has proven to have a predictive value towards life satisfaction.…”
Section: Tab4 Multiple Regression Analysis: Life Satisfaction Of Emmentioning
confidence: 99%
“…As may be noticeable, neither work to family conflict, nor family to work conflict have manifested themselves as important in the relationship with life satisfaction, which may be understood in terms of the expansionist hypothesis, which suggested that the advantages of pursuing multiple roles (from work to family, and vice versa) are likely to outweigh the disadvantages [52] [53] [54]. The results have supported this assumption as only enrichment has proven to have a predictive value towards life satisfaction.…”
Section: Tab4 Multiple Regression Analysis: Life Satisfaction Of Emmentioning
confidence: 99%
“…Os mitos e crenças que envolveram as conseqüências das atividades remuneradas das mulheres para sua saúde e bem-estar psicológico, e que criaram toda uma teoria de que estas deveriam permanecer em seus papéis tradicionais, vêm se diluindo a medida que as pesquisas realizadas a respeito da multiplicidade de papéis e bemestar psicológico têm encontrado níveis de bem-estar elevados entre mulheres que possuem um trabalho remunerado, em contraposição a níveis mais baixos em mulheres que não trabalham (Amatea & Fong, 1991;Aston & Lavery, 1993;Barnett & Baruch, 1985;Barnett & cols., 1992;Bullers, 1994;Gore & Mangione, 1983;Gove & Tudor, 1973;Hecht, 2001;Kandel, Davies & Raveis, 1985;Kessler & McRae, 1981;Kibria & cols., 1990;Martire & cols., 2000;Stephens & cols., 1994;Vandewater & cols., 1997;Verbrugge, 1983).…”
Section: Discussão E Conclusãounclassified
“…This thesis rests on two premises: first, people have only limited energy and time (Marks 1977); second, social organizations and institutions such as a company or the family demand all of a person's allegiance (Coser 1974). According to the thesis, people who have multiple roles do not have the energy and time to fulfill the demands of these roles and thus must make compromises (Barnett and Baruch 1985). Those with more roles are more likely to be exhausted because they cannot adequately perform all the duties -which leads to role strain or conflict and stress.…”
Section: The Theoretical Literaturementioning
confidence: 99%